The function of gestures within an interdisciplinary teaching sequence in music - Chatelain, Sabine (Swiss Journal of Educational Research, 2018)
Due to specific features of music, bodily dimensions play an important role within music education. These dimensions concern music practicing, music reception, as well as the music teaching and learning process. With respect to the concept of didactic transposition, we examine the role of bodily, receptive and didactical gestures within music education. Our research has been carried out with 14-15 year-old pupils participating at a case study including three interdisiplinary lessons on the theme «Free Jazz and Action painting». Results suggest to use gestures more consciously during all the steps of the didactical transposition process, including during the a priori analysis of the art work.